Pneumococcal serotypes in adults hospitalized with community-acquired pneumonia in Greece using urinary antigen detection tests: the EGNATIA study, November 2017 – April 2019. Issue 5 (30th November 2022) - Liapikou, Adamantia; Konstantinidis, Athanasios; Kossyvaki, Vasiliki; Skiadas, John; Menegas, Damianos; Méndez, Cristina; Beavon, Rohini; Begier, Elizabeth; Gessner, Bradford D.; Milionis, Haralampos; Tsimihodimos, Vasilios; Baxevanos, Gerasimos; et al.
ABSTRACT: Greece introduced a 13-valent pneumococcal conjugate vaccine (PCV13) into the infant national immunization program in 2010 (3 + 1 schedule until June 2019). Since 2015, PCV13 has been recommended for adults aged 19–64 years with comorbidities and adults ≥65 years sequentially with 23-valent pneumococcal polysaccharide vaccine (PPSV23). We examined pneumococcal serotype distribution among Greek adults aged ≥19 years hospitalized with community-acquired pneumonia (CAP) during November 2017-April 2019. This was an interim analysis of EGNATIA, a prospective study of adult hospitalized CAP in the cities of Ioannina and Kavala. Pneumococcus was identified using cultures, BinaxNow®, serotype-specific urinary antigen detection assays (UAD-1/2). Our analysis included overall 482 hospitalized CAP patients (mean age: 70.5 years; 56.4% male). 53.53% of patients belonged to the highest pneumonia severity index (PSI) classes (IV-V). Pneumococcus was detected in 65 (13.5%) patients, with more than half (57%) of cases detected only by UAD. Approximately two-thirds of pneumococcal CAP occurred in those aged ≥65 years (n = 40, 8.3% of CAP). More than half of pneumococcal CAP (n = 35, 53.8%) was caused by PCV13 serotypes. Most frequently detected PCV13 serotypes were 3, 19A, 23F, collectively accounting for 83% of PCV13 vaccine-type (VT) CAP and 6% of all-cause CAP. Overall, 82.9% of PCV13 VT CAP occurred among persons with an indication (age/risk-based) for PCV13 vaccination. Even with a mature PCV13 childhood immunization program, a persistent burden of PCV13 VT CAP exists in Greek adults. Strategies to increase PCV13 (and higher-valency PCVs, when licensed) coverage in adults should be implemented to reduce the disease burden. HIGHLIGHTS: An interim analysis of a prospective study in adults hospitalized with CAP in Greece. Serotype-specific urinary antigen detection assays were used to detect pneumococcus. A persistent burden of PCV13 vaccine-type CAP was observed in Greek adults. Improved PCV13 uptake and higher-valency PCVs may reduce the pneumococcal disease burden.